Sky color - Reynolds, Peter H. (Peter Hamilton), 1961- (Somerville, Mass. : Candlewick, 2012)
"Marisol loves to paint. So when her teacher asks her to help make a mural for the school library, she can't wait to begin! But wait-how can Marisol ever make a sky without blue paint? After gazing out the bus window and watching from her porch as day turns into night, she closes her eyes and starts to dream"--
Keywords: Artists -- Fiction; Paint -- Fiction; Color -- Fiction; Schools -- Fiction